Matematyka
ignacja13
2

1) Gdy a =-1 i b =3 , to wartość wyrażenia [latex]ab^{2} - \frac{1}{3} a^{2} b[/latex] jest równa : a) -10 b) -9 c) 9 d) 10 2) Wyrażenie [latex] (2x+1)^{2} -(2x-1)(2x+1)[/latex] jest równa : a) [latex] 8x^{2} [/latex] b) [latex] 8x^{2} +2[/latex] c) 4x +2 d) 4x 3) suma x^{2} -8x+16 rozłożona na czynniki to : a) x(x-4) b) (x-4)(x+4) c) (x-4)^{2} d) x(x-8) +4

+0
(1) Odpowiedź
Konto usunięte

1.a -1*3^2-1/3*(-1)^2*3= -1*9-1/3*1*3= -9-1= -10 2.c (2x+1)^2-(2x-1)(2x+1)=(2x+1)[(2x+1)-(2x-1)= (2x+1)*2= 4x+2 3.c x^2-8x+16=(x-4)^2

Dodaj swoją odpowiedź